2001
DOI: 10.1152/ajpregu.2001.281.4.r1134
|View full text |Cite
|
Sign up to set email alerts
|

Static handgrip exercise modifies arterial baroreflex control of vascular sympathetic outflow in humans

Abstract: To examine effects of static exercise on the arterial baroreflex control of vascular sympathetic nerve activity, 22 healthy male volunteers performed 2 min of static handgrip exercise at 30% of maximal voluntary force, followed by postexercise circulatory arrest (PE-CA). Microneurographic recording of muscle sympathetic nerve activity (MSNA) was made with simultaneous recording of arterial pressure (Portapres). The relationship between MSNA and diastolic arterial pressure was calculated for each condition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
84
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 32 publications
(57 reference statements)
14
84
2
2
Order By: Relevance
“…In this scenario, EAAs would exert a dual action on the vasomotor RVLM neurons by mediating the chemoreflex or metaboreflex-evoked sympathoexcitation and also by increasing the sympathetic baroreflex responsiveness to changes in blood pressure. The previous findings that static exercise is accompanied by a strong increase in the gain of the muscle sympathetic baroreflex while hypoxia increases the RSNA baroreflex gain are in line with such a possibility (24,28). This can be regarded as a protective mechanism that buffers an excessive sympathoexcitation evoked by these reflexes to optimize the cardiovascular homeostasis in a given physiological or pathological situation.…”
Section: Perspectivesmentioning
confidence: 55%
“…In this scenario, EAAs would exert a dual action on the vasomotor RVLM neurons by mediating the chemoreflex or metaboreflex-evoked sympathoexcitation and also by increasing the sympathetic baroreflex responsiveness to changes in blood pressure. The previous findings that static exercise is accompanied by a strong increase in the gain of the muscle sympathetic baroreflex while hypoxia increases the RSNA baroreflex gain are in line with such a possibility (24,28). This can be regarded as a protective mechanism that buffers an excessive sympathoexcitation evoked by these reflexes to optimize the cardiovascular homeostasis in a given physiological or pathological situation.…”
Section: Perspectivesmentioning
confidence: 55%
“…It was demonstrated that change in forearm position may have an impact on sympathetic nerves in muscles of hand 35) . However, reports are concentrated on forearm raise together with handgrip exercises performed more or less intensively, which could cause the increase in sympathetic activity 35,36) . For these reasons we think that results of our experiments were not ultimately interfered by holding a telephone.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the control exerted by the arterial baroreflexes (carotid and aortic baroreflexes together) over muscle sympathetic nerve activity (MSNA) has been shown to be elevated during both static handgrip exercise and PEMI (8,9). Very recently, Ichinose et al (6) reported that the modification of the arterial baroreflex control of MSNA that is seen during PEMI could be a consequence of a muscle metaboreflex-induced alteration in the baroreflex control of both the occurrence and strength of MSNA bursts.…”
mentioning
confidence: 99%